2004
DOI: 10.1111/j.1365-2958.2003.03951.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial condensin/cohesin‐like protein complex acts in DNA repair and regulation of gene expression

Abstract: SummaryStructural maintenance of chromosome (SMC) and the SMC-interacting kleisin protein families have key functions in the chromosome organization of most organisms. Here, we report that the Bacillus subtilis kleisin, ScpA, can form a ternary complex with the SMC and ScpB proteins in a yeast tri-hybrid assay, supporting the notion of a bacterial cohesin/condensin-like complex. Furthermore, ScpA interacts in two-hybrid assays with the AddAB complex, essential for recombinational repair, with DegS, a twocompon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 46 publications
7
52
1
Order By: Relevance
“…Interestingly, ScpA has been shown to interact with transcription factors and several additional proteins in a two-hybrid system, and to affect the function of a two-component system regulating sugar metabolism (Dervyn et al, 2004). In any event, the defect in protein synthesis in smc mutant cells could be almost entirely cured by overproduction of Topo IV, indicating that the defect of the smc deletion is due to a lack of supercoiling, which can be rescued by increased Topo IV activity.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, ScpA has been shown to interact with transcription factors and several additional proteins in a two-hybrid system, and to affect the function of a two-component system regulating sugar metabolism (Dervyn et al, 2004). In any event, the defect in protein synthesis in smc mutant cells could be almost entirely cured by overproduction of Topo IV, indicating that the defect of the smc deletion is due to a lack of supercoiling, which can be rescued by increased Topo IV activity.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, Smc2 and Smc4 are involved in X chromosome gene dosage compensation and mitotic chromosome condensation (e.g., see references 85 to 87). Chromosome organization and segregation in B. subtilis are accomplished by the SMC complex, which includes SMC, ScpA (kleisin), and ScpB (35,36,144,214,246,395,400) (98). In support of a role for ScpA in homologous recombination, point mutations in ScpA were identified that rendered cells sensitive to mitomycin C challenge (98).…”
Section: Potential Roles For Other Smc-like Proteins In Dsb Repairmentioning
confidence: 99%
“…These results imply that the bacterial SMC complex may be much closer to condensins than cohesin. Nevertheless, evidence is also available that B. subtilis SMC (or its distant relative MukB in E. coli) may have cohesin-like functions such as keeping together the newly replicated sister DNAs (Sunako et al 2001;Lindow et al 2002b) or promoting DNA repair (Dervyn et al 2004). From an evolutionary point of view, bacterial SMC proteins belong to the main branch of the SMC family that includes SMC1, SMC2, SMC3, and SMC4 but not SMC5 or SMC6 (Cobbe and Heck 2004).…”
Section: Bacterial Smc Linkersmentioning
confidence: 99%